Absolute calibration of a large-diameter light source - Brack, J. T. (2013)
A method of absolute calibration for large aperture optical systems is presented, using the example of the Pierre Auger Observatory fluorescence detectors. A 2.5 m diameter light source illuminated by an ultra-violet light emitting diode is calibrated with an overall uncertainty of 2.1 % at a wavelength of 365 nm.